PHRASAL VERB IN COLDPLAY’S ALBUM SONG A HEAD FULL OF DREAMS - Indera Nivika; Indri Kustantinah; Festi Himatu Karima (Journal of English Language Teaching and Literature (JELTL), 2023)
This article is about Phrasal Verb found in Coldplay’s Song Album A Head Full of Dream and its contribution to vocabulary learning. The researchers utilized a descriptive qualitative method as the data is not numerical but instead taken from the lyrics of the songs in the form of words and phrases. The object of the research is phrasal verbs in Coldplay’s Song Album A Head Full of Dream. There are eleven songs on the album: A Head Full of Dreams, Birds, Hymn of the Weekend, Everglow, Adventure of a lifetime, Fun, The Scientist, Army of One, Amazing Day, Yellow, and Up & Up. There are fifty-six phrasal verbs found in the album that are divided into three types; transitive separable, transitive inseparable, and intransitive inseparable. It is possible that Coldplay’s album A Head Full of Dreams is a useful material to improve vocabulary building on phrasal verb since there are numerous phrasal verbs. This can provide students with much-needed exposure to challenging aspects of the English language, such as phrasal verbs. This is especially true in the English as a Foreign Language context, where the majority of learners' exposure is limited to the teaching. The use of songs from Coldplay's album is also emerging as an innovative method of teaching phrasal verbs. It is also a significant development in terms of how to teach phrasal verbs